Biosynthesis, Characterization, Adsorption and Antimicrobial studies of zirconium oxide Nanoparticles Using Punica Granatum Extract - Abdul Karem, Lekaa k.; Tariq Ali, Angham; Ewies F. Ewies (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this study we using zirconium sulfate, Punica granatum plant extract, and an alkaline medium, to created ZrO2 nanoparticles. They were then characterized using a variety of techniques, including FT-IR, UV-visible, atomic force microscopy, X-ray diffraction, transmission electron microscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The Debye-Scherrer equation was used to calculate the crystal size in X-ray diffraction and found to be 27.82 nm. The particle size of ZrO2 nanoparticles was determined using atomic force microscopy, scanning electron microscopes, and transmission electron microscopy. Utilizing ZrO2 NPs, the metal ions M (II) = Co, Ni, and Cu were successfully adsorbed, proving that the three metal ions could be removed from the water at the same time. Over the time frame and under the circumstances, Ni(II) has the highest rate of adsorption. Co, Ni, and Cu ions had removal efficiencies of 32.79%, 75.00%, and 30.20%, respectively. Three concentrations of the ZrO2 nanoparticles were tested against two types of bacteria, Escherichia coli and staphylococcus, and one type of fungus, Candida, in various concentrations of (25, 50, and 75) mg/L. The outcomes were contrasted with those attained using the medications Amoxicillin and Metronidazole.